2018
DOI: 10.1139/cjc-2018-0077
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and self-assembly of thiol-modified tellurophenes

Abstract: An asymmetric thiol-modified tellurophene was designed and synthesized, and the ability of the compound to form a monolayer on a gold electrode was confirmed. The surface-active tellurophene was synthesized using Cadiot–Chodkiewicz coupling followed by ring closing and thiol modification. The tellurophene compound forms a monolayer on gold surfaces from a concentrated solution within 24 h. The ability of the compound to conjugate to gold is confirmed by X-ray photoelectron spectroscopy (XPS). A surface blockin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…To verify the existence of unoxidized Te inside of NPs, the NPs surface was etched for 20 nm depth for XPS . Figure E showed that two peaks at 573.2 and 583.6 eV were observed, which were assigned to unoxidized Te, suggesting that tellurophene exists in the NPs . Moreover, the other two weak peaks at 576.2 and 586.7 eV indicated the oxidation of tellurophene was inevitable.…”
Section: Figurementioning
confidence: 99%
“…To verify the existence of unoxidized Te inside of NPs, the NPs surface was etched for 20 nm depth for XPS . Figure E showed that two peaks at 573.2 and 583.6 eV were observed, which were assigned to unoxidized Te, suggesting that tellurophene exists in the NPs . Moreover, the other two weak peaks at 576.2 and 586.7 eV indicated the oxidation of tellurophene was inevitable.…”
Section: Figurementioning
confidence: 99%
“…To verify the existence of unoxidized Te inside of NPs, the NPs surface was etched for 20 nm depth for XPS . Figure E showed that two peaks at 573.2 and 583.6 eV were observed, which were assigned to unoxidized Te, suggesting that tellurophene exists in the NPs . Moreover, the other two weak peaks at 576.2 and 586.7 eV indicated the oxidation of tellurophene was inevitable.…”
Section: Figurementioning
confidence: 99%